체질량지수에 따른 일부 대학생의 체형인식도와 식행동에 관한 연구 - 김시연(Si Yeon Kim); 이홍미(Hong Mie Lee); 송경희(Kyung Hee Song) (Korean journal of community nutrition, 2007)
This study was performed to investigate the body image perception by BMI and the dietary behaviors in 803 college students(408 males and 395 females). The degree of obesity was divided into an underweight group with BMI less than $18.5kg/m^2$, a normal group with BMI of $18.5{\sim}22.9kg/m^2$, an overweight group with BMI of $23{\sim}24.9kg/m^2$ and an obese group with BMI over $25.0kg/m^2$. The average ages of subjects were 22.9 years in males and 20.2 years in females. The average weight and height of male subjects were 175.3 cm and 69.6 kg, respectively and those of female subjects were 162.5 cm and 52.0 kg, respectively. The average BMIs of male and female subjects were $22.6kg/m^2$ and $19.7kg/m^2$, respectively. The distribution of subjects who perceived their current body image as ideal body image was 25.7% in males and 10.9% in females, showing that the body image satisfaction of male subjects was 1.5 times higher than that of female subjects. Body image perception for their own bodies was mostly shown as the average or standard shape both in males and females with 64.2% and 54.2%, respectively, but males showed a higher perception rate than females and 31.1% of females and 19.5% of males perceived their bodies as lean shape(p<0.01). The body image satisfaction was 4.20 in males and 3.70 in females, showing more satisfaction in the male subjects(p<0.001). The correlation between body image and physical variables in male subjects indicated that CBI and IBI showed statistically significant correlation and also BMI showed statistically significant correlation with IBI(p<0.001) and CBI(p<0.001). The frequency of eating out increased as the frequency of skipping meals increased(p<0.001) and the frequency of having snacks increased as the frequency of eating out increased(p<0.01). The correlation between body image and physical variables in female subjects showed that CBI and IBI(p<0.001) had statistically significant correlation. Body weight showed statistically significant correlation with CBI(p<0.001), BMI(p<0.001) and height(p<0.001). The frequency of eating out increased as height(p<0.01) and the frequency of skipping meals(p<0.001) increased. When both male and female subjects wanted leaner body shapes, they preferred much leaner shapes despite their current body images belonging in the normal range. Additionally subjects preferred the body image in the normal range in cases when their current body images were lean. In particular, more female subjects had strong desires to become leaner in their body images than male subjects, which could be analyzed as a risk factor for physical him. From the above results, it is considered that both male and female subjects need to establish proper recognition and dietary behaviors for their body images and also need nutritional education and counseling for desirable weight control methods.